Micronutrients in Multiple Pregnancies—The Knowns and Unknowns: A Systematic Review - Zgliczynska, Magdalena (Nutrients, 2021)
Maternal diet and nutritional status are of key importance with regard to the short- and long-term health outcomes of both the mother and the fetus. Multiple pregnancies are a special phenomenon in the context of nutrition. The presence of more than one fetus may lead to increased metabolic requirements and a faster depletion of maternal macro- and micro- nutrient reserves than in a singleton pregnancy. The aim of this systematic review was to gather available knowledge on the supply and needs of mothers with multiple pregnancies in terms of micronutrients and the epidemiology of deficiencies in that population. It was constructed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement (PRISMA). The authors conducted a systematic literature search with the use of three databases: PubMed/MEDLINE, Scopus and Embase. The last search was run on the 18 October 2020 and identified 1379 articles. Finally, 12 articles and 1 series of publications met the inclusion criteria. Based on the retrieved studies, it may be concluded that women with multiple pregnancies might be at risk of vitamin D and iron deficiencies. With regard to other microelements, the evidence is either inconsistent, scarce or absent. Further in-depth prospective and population studies are necessary to determine if nutritional recommendations addressed to pregnant women require adjustments in cases of multiple gestations.